Risk assessment for chemical substances: the link between toxicology and public health Avaliação de risco de substâncias químicas: o elo entre a toxicologia e a saúde pública - Francisco J. R. Paumgartten (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1993)
Virtually all chemical substances may cause adverse health effects, depending on the dose and conditions under which individuals are exposed to them. Toxicology - the study of harmful effects of chemicals on living organisms - provides the scientific data base on which risk assessment of adverse health effects stands. Risk assessment (RA) is the process of estimating the probability that a chemical compound will produce adverse effects on a given population, under particular conditions of exposure. Risk assessment process consists of four stages: Hazard Identification (HI), Exposure Assessment (EA), Dose-Response Assessment (DRA), and Risk Characterization (RC). The risk assessment process as a whole makes it possible to carry out cost(risk)/benefit analysis, and thus risk management, on a rational basis. A capacity to undertake risk assessment is thus sine qua non for making decisions that are concerned with achieving a balance between economic development and adequate protection of public health and the environment. Virtualmente todas as substâncias químicas podem causar efeitos adversos, dependendo da dose e das condições em que os indivíduos são a elas expostos. A toxicologia, isto é, o estudo dos efeitos danosos de substâncias químicas em organismos vivos, fornece a base de dados científicos na qual se apoia a avaliação de risco de efeitos adversos para a saúde. Avaliação de Risco (AR) é o processo de se estimar a probabilidade que um composto químico tem de vir a produzir efeitos adversos numa dada população, em determinadas condições de exposição. A avaliação de risco consiste de quatro estágios: identificação da periculosidade (IP); avaliação da exposição (AE); avaliação da relação dose-efeito (ADE); e caracterização do risco (CR). O processo de avaliação de risco como um todo possibilita a realização da análise custo (risco)/benefício e, portanto, do gerenciamento do risco, em bases racionais. A capacidade de se realizar a avaliação de risco é, assim, condição sine qua non para a tomada de decisões que estejam voltadas para se alcançar um equilíbrio entre desenvolvimento econômico e uma adequada proteção da saúde pública e do meio ambiente.